Perlindungan Hukum terhadap Tenaga Kerja Outsourcing dalam Perjanjian Kerja Outsourcing - Florencia Lavina Setiawan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
One of the main strategies companies employ to compete in the business world is production cost efficiency, as controlling expenses is a crucial factor in maintaining competitiveness and increasing profitability. As one solution, many companies implement an outsourcing system. Through this mechanism, certain functions or activities are delegated to a third party with specialized expertise, allowing the company to reduce operational burdens, reduce costs, and focus more on its core business activities. Thus, outsourcing is seen as a strategic step to increase efficiency while strengthening the company's position in the face of global competition.